Nonlinear wind-drift ocean currents in arctic regions. Issue 2 (4th March 2022) - Constantin, Adrian
Abstract : We rely on the f -plane approximation to derive the nonlinear governing equations for arctic wind-drift flow in regions that are not in the vicinity of the North Pole. An exact solution is derived in the material (Lagrangian) framework, a setting suitable for the accurate description of the particle paths. This approach facilitates the identification of oscillations superimposed on a mean spiralling Ekman current.